(untitled) - Martin, James W. (New York, 2007)
Lean Six Sigma for Supply Chain Management contains specific information for developing inventory models, metrics for aligning objectives with strategic goals, a concise overview of supply chain concepts, and models illustrating how lead time and demand impact customer service and inventory investment levels. This vital resource features: A complete program for Lean Six Sigma improvement and control; The latest Lean Six Sigma methods to identify and manage supply chains; Expert help with Lean Six Sigma supply chains and third party logistics; Applications of Lean Six Sigma to MRPII; Guidance on root-cause analysis using Six Sigma tools.
Keywords: Business logistics,Six sigma (Quality control standard)